Doctor's Responsibilities With the Issuance of A Health Certificate Based on Law and Medical Ethic - Susanti, Yulia; Azheri, Busyra; Mannas, Yussy Adelina; Hasbi, Muhammad; Syofyan, Syofirman (Dinasti Research, 2026)
This study examines the responsibilities of doctors in issuing health certificates, which often become a source of legal and ethical issues. The background of the problem is the importance of health certificates as administrative documents that can influence various decisions, yet specific regulations regarding their issuance have not been deeply regulated. The objective of this research is to analyze the responsibilities of doctors in issuing health certificates based on Indonesian law and medical ethics. The research method used is normative juridical by examining secondary legal materials. The results indicate that a doctor's responsibilities encompass ethical, professional, and legal aspects (administrative, civil, criminal). Violations can result in ethical, administrative, civil, or criminal sanctions. In conclusion, doctors must issue health certificates accurately, honestly, and based on careful medical examinations, in accordance with the law and professional ethics to avoid harm to related parties and legal claims.